Biological Diversity of Wild Bird Species in the Desert Region and their Ecological Functions in the Agroecosystem - Adilov Sobitjon Uktamovich; Umirov Ismoil Eshonqulovich; Umirzoqov Jamshid Mirzayevich (American Journal of Botany and Bioengineering, 2025)
The article examines the biological diversity of wild bird species found in the territory of the Central Kyzylkum National Nature Park, their ecological role in the habitat, their importance in natural pest control, and their functions within the agroecosystem. During the research, more than 50 bird species were identified based on regular observations by scientific staff in the park area and categorized into ecological groups. Additionally, factors causing the decline in bird populations were analyzed, and recommendations for their conservation were provided.